The Effect of in Vitro Sample Preparation Methods on Bond Strength of Mineral Trioxide Aggregate to Root Dentin - Samiei, Mohammad; Torab, Ali; Abdollahi, Amir Ardalan; Rostami, Parisa (Iranian Endodontic Journal, 2020)
Introduction: The aim of this study was to compare the effect of sample preparation methods on push-out bond strength of mineral trioxide aggregate (MTA). Methods and Materials: Twenty-four extracted human mandibular premolars with single root canal were selected for this in vitro study. After instrumentation, irrigation and drying of root canals, they were randomly divided into two experimental groups (n=12). Group 1: After removing the 3 mm of root ends, 2 mm thick sections were established from the remaining roots. MTA was mixed following the manufacturers’ recommendations and root sections were filled. Group 2: The whole root canal was used for filling and packing of MTA and like group 1, after removing the 3 mm of root ends, root sections were provided. Push-out bond strength was measured and analyzed by the independent t-test. Level of statistical significance was set at 0.05. Results: The highest mean push-out bond strength was in apical section of group 2 (4.86±1.31) and the lowest value was in coronal section of group 2 (3.05±1.15). The results of the independent t-test showed a significant difference between two groups only in the apical section (P=0.02). Conclusion: Based on the results of this in vitro study, the highest mean push-out bond strength was in apical section of group 2. It seems that using the whole root canal for MTA application is better for MTA in vitro analysis of bond strength to root dentin because it is more similar to the clinical conditions. Keywords: Bond Strength; Endodontics; Mineral Trioxide Aggregate; Root Dentin